ANALISYS OF EMPLOYEE WORK DISCIPLINE IN TANDANGSARI MULTIPLE BUSINESS COORPERATIVES SUMEDANG hal 27 - 35 - Gustina Hidayat (Journal of Bussines Management Basic, 2023)
This study aims to determine how the work discipline of employees at the Multipurpose Cooperative of Tandangsari Sumedang and how to improve the work discipline of these employees. The method used in this research is a qualitative research method that is natural and the data collection technique is purposive sampling technique. The results of the study indicate that the level of work discipline of employees at the Multipurpose Coorperative of Tandangsari Sumedang is considered to be still not optimal in its application from some employees. The obstacles to work discipline faced by the Coperative at this time are that there are still employees who are often late for work and some even don’t come to work without clear information, there are employees who are negligent in working for the sake of personal interest then there are employees who are not responsible for their work, and the lack of employee awareness of the importance of work discipline.